Coordination Structure of Titanium Ions in Molten LiF-KF Mixture with the Addition of TiO2 and Bulk Titanium. Issue 12 (1st December 2022) - Okada, Kaai; Suzuki, Yuta; Fukunaka, Yasuhiro; Goto, Takuya
Abstract : The difference between Ti(III) and Ti(IV) significantly influences the electrodeposition process of Ti in fluoride melt. In this study, we investigated the melt structure of LiF-KF with the addition of TiO2 for Ti(IV) and with the addition of both TiO2 and bulk titanium (Ti 0 ) for Ti(III) by combining high-temperature Raman spectroscopic technique and density functional theory calculations. The Raman spectra were characterized by three kinds of coordination structures: polyatomic ion-like structures such as TiO2 F2 2−, polyatomic cation-coordinated ion-like structures such as [TiF6 −K] −, and molecule-like structures such as TiOF3 −K. The results showed that the K + ions are more likely to form structures with the titanium oxyfluorides. We also found that the melt with and without Ti 0 showed almost completely different Raman bands. The information gained in this study for the coordination structure around titanium ions in the fluoride melts is significant towards the electrodeposition process of titanium-based materials in fluoride melt and marks an important step towards further understanding of the dissolution process of titanium oxyhalide structure in the melt.